2023
DOI: 10.1021/acsami.2c20580
|View full text |Cite
|
Sign up to set email alerts
|

Simple Way to Fabricate Emissive Boron-Containing Covalent Organic Frameworks

Abstract: Highly fluorescent covalent organic frameworks (COFs) are rarely obtained because of the π–π stacked layers with aggregation-caused quenching behavior. Unarguably, highly fluorescent COFs with tunable emission colors are even more rarely achieved. Herein, a general strategy to modify the classical COF material (named COF-1) by different fluorescent molecules via N → B interaction was developed. In this method, the boron-containing COF-1 acted as a porous and crystalline matrix as well as a reaction partner of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 57 publications
(81 reference statements)
0
9
0
Order By: Relevance
“…1e, AlPc-TB POP showed quite broad diffraction peaks located at 2q ∼ 22.3°and 45.7°, suggesting that the sample has no long-range structure and is amorphous, which is similar to the reported POPs containing TB segments. 35,36 The stability of the sample at high temperature was studied using TGA (Fig. 1f).…”
Section: Materials Characterizationmentioning
confidence: 99%
“…1e, AlPc-TB POP showed quite broad diffraction peaks located at 2q ∼ 22.3°and 45.7°, suggesting that the sample has no long-range structure and is amorphous, which is similar to the reported POPs containing TB segments. 35,36 The stability of the sample at high temperature was studied using TGA (Fig. 1f).…”
Section: Materials Characterizationmentioning
confidence: 99%
“…For example, Ma's group explored the tunable fluorescence of boroxine COFs coordinated with a range of N‐donating triphenylamine (TPA) substituted pyridines ( 36 , Figure 9a). [66] After incorporating the pyridine dyes on the surface of COF‐1, the emission intensities were greatly enhanced. The emission wavelengths were red‐shifted relative to the unbound pyridyl‐amine dyads because B−N coordination promoted ICT by lowering the electron density on the Py ring.…”
Section: Supramolecular Network Polymersmentioning
confidence: 99%
“…Ma et al developed a series of COF based amine sensors using COF-1, a phenyl diboronic acid-based COF first reported by Yaghi et al 132,133 While COF-1 is non-emissive, the authors found that incorporating emissive pyridine-containing dyes a series of emissive dye-COF hybrids could be developed (Fig. 8a).…”
Section: Covalent Organic Framework Based Fluorescence Sensorsmentioning
confidence: 99%
“…Electrochemical sensors, like fluorescent sensors, are highly sensitive and generally exhibit low LODs. However, they are 133 This journal is © The Royal Society of Chemistry 2023 more difficult to develop as sensors for food packaging than their colorimetric and fluorescent sensor counterparts due to requiring electrodes and a power source. What is advantageous about electrochemical sensors is their potential to be made reusable due to non-destructive sensing modes that are reversible, therefore, they remain economical regardless of a high production cost.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%